Ploidy variation in hybrids from interploid 3x X 2x crosses in Musa - Osuji, J.O.; Vuylsteke, D.R.; Ortíz, R. (1998)
Hybrids were obtained after in vitro germination of embryos from interploid crosses between triploid ‘French' plantain cultivars (Musa spp. AAB group). ‘Ntanga 2' and ‘Bobby Tannap' with diploid banana (Musa acuminata subsp. burmannicoides) ‘Calcutta 4'. Cross-pollinated bunches were harvested at full maturity and ripened with acetylene in a room for 4 days. Seeds were extracted from peeled ripe fruits by squashing. Embryos from the seeds were excised aseptically after 2 days and germinated in vitro. Seedlings were subsequently planted in early evaluation trials after acclimatizing in the greenhouse. Chromosome counts were carried out on root tips of mature and maiden suckers to determine ploidy levels using a modified squashing technique. Counts showed that two of the hybrids were aneuploids (trisomics) with somatic chromosome number of 2n = 2x + 1 = 23. One hybrid was diploid while the other two were tetraploids. Tetraploids are the most promising hybrids for the genetic improvement of plantains. Diploids are valuable material for further improvement of the plantain genome at this ploidy level. Trisomics provide means for further characterization of the Musa genome and physical gene mapping in plantain and banana.